2013
DOI: 10.1039/c3cc41250d
|View full text |Cite
|
Sign up to set email alerts
|

A novel tellurophene-containing conjugated polymer with a dithiophenyl diketopyrrolopyrrole unit for use in organic thin film transistors

Abstract: A new tellurophene-based π-conjugated polymer, PDTDPPTe, was synthesized. PDTDPPTe exhibits a smaller optical band gap (E(g)(opt) = 1.25 eV) than thiophene-based PDTDPPT (E(g)(opt) = 1.30 eV). Thin-film transistors comprising PDTDPPTe displayed outstanding performance (μ(max) = 1.78 cm(2) V(-1) s(-1), I(on)/I(off) = 10(5-6)).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 29 publications
0
40
1
Order By: Relevance
“…321 P212 containing a thiophene-flanked DPP acceptor and a tellurophene donor shows a smaller band gap (1.25 eV) than P210. 322 The smaller P212 band gap is due to the more electron-rich character of the Te atom as compared to the S atom, which elevates the P212 HOMO to −5.13 eV in comparison to the −5.38 eV HOMO of thiophene-based polymer P210. The smaller energy barrier between P212 HOMO and Au electrode work function results in more facile hole injection, which leads to an enhanced P212 μ h of 1.47 cm 2 /(V s) in comparison to P210 μ h of 0.62 cm 2 /(V s) in the optimized OTFTs.…”
Section: Synthesis Of Dibrominated Diketopyrrolopyrrolementioning
confidence: 98%
“…321 P212 containing a thiophene-flanked DPP acceptor and a tellurophene donor shows a smaller band gap (1.25 eV) than P210. 322 The smaller P212 band gap is due to the more electron-rich character of the Te atom as compared to the S atom, which elevates the P212 HOMO to −5.13 eV in comparison to the −5.38 eV HOMO of thiophene-based polymer P210. The smaller energy barrier between P212 HOMO and Au electrode work function results in more facile hole injection, which leads to an enhanced P212 μ h of 1.47 cm 2 /(V s) in comparison to P210 μ h of 0.62 cm 2 /(V s) in the optimized OTFTs.…”
Section: Synthesis Of Dibrominated Diketopyrrolopyrrolementioning
confidence: 98%
“…The ICT band is redshifted when compared with that of MPU1 (702 nm) due to the higher polarizability of the selenium environment . Selenium is larger than sulfur and this results in a lower aromatic resonance energy for selenophene (1.26 vs 1.56 eV for thiophene) due to the poor overlap of the selenium orbitals with the π‐system of the carbon framework . This effect increases the quinoidal contribution to the molecular structure and therefore extends the absorption profile toward the longer wavelength region.…”
Section: Resultsmentioning
confidence: 99%
“…Properties critical to polymer perfor-mance such as molecular weight, polydispersity, and regioregularity are controlled by the efficiency and regioregularity of the specific coupling reactions used for polymerization. In comparison with poly(3-alkylthiophene)s, Seferos and co-workers have observed red-shifted absorption spectra and smaller bandgaps from poly(3-alkyltellurophene)s. [9] In a related development, Choi and coworkers have prepared a tellurophene-containing lowbandgap polymer by Stille cross-coupling and reported that replacing sulfur atoms with tellurium atoms in conjugated polymers reduces the bandgap and improves the hole mobility, [10] potentially enhancing the performance of OPV materials. The formation of arylaryl bonds through the cleavage of aryl-carbon bonds would allow polymerization to proceed without the need for reactive inorganic leaving groups, however, there are a limited number of examples of such reactions because of the high bond dissociation energy for carbon-carbon bonds.…”
mentioning
confidence: 99%
“…The longer triplet exciton lifetimes should increase exciton diffusion lengths allowing more photocurrent collection and result in higher solar cell power conversion efficiencies (PCEs). Herein, we describe the first example of palladium-catalyzed ipso-arylative copolymerization of a tellurophene monomer (1) with a diketopyrrolopyrrole (DPP) unit (2) (Scheme 1), in a method complementary to widely used Stille [10] and Suzuki-Miyaura polymerizations, and demonstrate use of the resulting polymer in photovoltaic devices. Herein, we describe the first example of palladium-catalyzed ipso-arylative copolymerization of a tellurophene monomer (1) with a diketopyrrolopyrrole (DPP) unit (2) (Scheme 1), in a method complementary to widely used Stille [10] and Suzuki-Miyaura polymerizations, and demonstrate use of the resulting polymer in photovoltaic devices.…”
mentioning
confidence: 99%